2020
DOI: 10.1002/ijgo.13163
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of D‐dimer tested by immunoturbidimetry are associated with the extent of severity of pre‐eclampsia

Abstract: Objective To establish the association between increased levels of D‐dimer and severity of pre‐eclampsia. Methods A nested, prospective cohort, analytical case–control study was conducted among women with pre‐eclampsia between March 2017 and March 2018. Inclusion criteria were age over 18 years, gestational age of more than 20 weeks, a single pregnancy with a living fetus, and a diagnosis of pre‐eclampsia. D‐dimer was measured by immunoturbidimetry at the time of diagnosis of pre‐eclampsia, applying cut‐off po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Further, in the second trimester of pregnancy, D-dimers were positively correlated with fibrinogen (r = 0.475; p 0.001). Rodríguez-Peña and Ibáñez-Pinilla (17) discovered a correlation between high D-dimer levels and the severity of pre-eclampsia. They also found a link between elevated D-dimer levels and the severity of preeclampsia, lending credence to the idea that the activation of fibrinolysis and the coagulation system is a key physiopathologic component of the disease.…”
Section: Resultsmentioning
confidence: 98%
“…Further, in the second trimester of pregnancy, D-dimers were positively correlated with fibrinogen (r = 0.475; p 0.001). Rodríguez-Peña and Ibáñez-Pinilla (17) discovered a correlation between high D-dimer levels and the severity of pre-eclampsia. They also found a link between elevated D-dimer levels and the severity of preeclampsia, lending credence to the idea that the activation of fibrinolysis and the coagulation system is a key physiopathologic component of the disease.…”
Section: Resultsmentioning
confidence: 98%
“…In another study, Chu et al [ 24 ] found that as HDPs worsened, DD, Fib, and vWF: Ag levels increased significantly higher in mild, moderate, and severe patients, as compared with controls. Rodríguez-Peña et al [ 25 ] used an immunoturbidimetric assay to detect DD and found that elevated levels of DD were strongly associated with SPE. This further demonstrated that fibrinolytic activation and the activation of the coagulation system may be involved in the pathogenesis of SPE.…”
Section: Discussionmentioning
confidence: 99%
“…Preeclamptic women are more likely to suffer PPH than low-risk women (10% VS 0.4-1.3%) [ 20 ]. Significantly higher D-dimer plasma levels were found in sPE group than those in mPE group [ 3 , 21 , 22 ], suggesting the more aggressively activated coagulation and fibrinolysis systems in severe preeclampsia [ 17 ], which might lead to more blood loss in sPE women. The D-dimer plasma level increased gradually with the increase of gestational age during normal pregnancy [ 5 , 21 , 23 ].…”
Section: Discussionmentioning
confidence: 99%